2014
DOI: 10.1002/jbm.a.35260
|View full text |Cite
|
Sign up to set email alerts
|

How can bioactive glasses be useful in ocular surgery?

Abstract: In the last few decades, the introduction of bioactive glasses (BGs), a special class of bioceramics that are able to bond to living tissues stimulating new tissue growth, has improved both treatment procedures via reconstructive surgery and the quality of life of rehabilitated patients in orthopedics and dentistry. While BGs have been extensively investigated for applications in these two surgical fields, there has been relatively little research on their use in other medical areas. Glass has been used for ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 100 publications
0
23
0
Order By: Relevance
“…Deposition of a MBG coating onto a non-absorbable porous substrate can be a valuable option whenever a permanent base structure is required: this is the case of orbital implants that have to safely replace the ocular globe in enucleated people upon the patient's whole lifetime without the need for subsequent surgical substitution [118]. In this regard, Ye et al [119] coated porous hydroxyapatite orbital implants (pore size within 200-500 lm) with a thin layer of CuO-containing MBG (Cu-MBG) to exploit a double antibacterial action: on one hand the antibacterial effect of Cu 2+ ions released as the coating degrades (copper shows potent antiseptic activity in suppressing a range of bacterial pathogens involved in hospital-acquired ocular infections [120]) and, on the other hand, the antibacterial effect of ofloxacin released from the coating mesopores.…”
Section: Coated Systemsmentioning
confidence: 99%
“…Deposition of a MBG coating onto a non-absorbable porous substrate can be a valuable option whenever a permanent base structure is required: this is the case of orbital implants that have to safely replace the ocular globe in enucleated people upon the patient's whole lifetime without the need for subsequent surgical substitution [118]. In this regard, Ye et al [119] coated porous hydroxyapatite orbital implants (pore size within 200-500 lm) with a thin layer of CuO-containing MBG (Cu-MBG) to exploit a double antibacterial action: on one hand the antibacterial effect of Cu 2+ ions released as the coating degrades (copper shows potent antiseptic activity in suppressing a range of bacterial pathogens involved in hospital-acquired ocular infections [120]) and, on the other hand, the antibacterial effect of ofloxacin released from the coating mesopores.…”
Section: Coated Systemsmentioning
confidence: 99%
“…In these "traditional" applications, glass has been employed as an optical element of ophthalmic devices; in recent years, some highly innovative applications of bioactive glasses and glass-ceramics have emerged to impart key added values to ocular implants, such as angiogenesis and antibacterial properties [86].…”
Section: Ocular Applicationsmentioning
confidence: 99%
“…101 This property can be helpful to accelerate wound healing, as shown in some animal studies (rat model). [102][103][104] Based on this evidence, Baino first suggested in 2015 105 that the Cu-doped MBG coating developed by Ye et al 91 could be useful to promote fibrovascularization in porous orbital implants due to controlled delivery of copper ions. This hypothesis was actually verified in vivo in 2018 by Ye's group, 106 who performed primary angiogenic tests in a panniculus carnosus muscle model in rabbits and reported that the Cu-doped glass coating significantly accelerated the vascularization of porous hydroxyapatite orbital implants compared to Cu-free materials.…”
Section: Improving Fibrovascularizationmentioning
confidence: 99%